2019
DOI: 10.1007/s40430-019-1831-7
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the mechanical and tribological behaviours of different aluminium matrix–ceramic composites

Abstract: Aluminium matrix composites (AMCs) have great potential for critical applications within aerospace, automotive, defence, marine, agriculture and nuclear engineering sectors. The composite materials are very attractive because of their good balance between lightweight versus high strength and machinability. Depending on the particular application, these properties can be further enhanced by adding silicon carbide, boron carbide and graphite, respectively. These reinforcements help to upscale the physical/mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…However, multiple particulate reinforcements in the PRAMCs improve wear resistance extensively. Different materials have been synthesized by multiple reinforcements with promising results [6][7][8][9], but the work is limited with Al 3 Zr and ZrB 2 combination [1,[10][11][12]. The Al 3 Zr exhibits low density, high melting point and high elastic modulus with excellent resistance to oxidation and corrosion [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, multiple particulate reinforcements in the PRAMCs improve wear resistance extensively. Different materials have been synthesized by multiple reinforcements with promising results [6][7][8][9], but the work is limited with Al 3 Zr and ZrB 2 combination [1,[10][11][12]. The Al 3 Zr exhibits low density, high melting point and high elastic modulus with excellent resistance to oxidation and corrosion [2].…”
Section: Introductionmentioning
confidence: 99%
“…The target test piece is constructed as two sheets of 4 mm thick transparent glass sandwiched between a 4 mm thick alumina aerogel translucent material layer. The structure of the comparative test piece was a translucent film attached to ordinary 4 m thick flat glass [18]. This ensures that the light transmittance of the contrast specimen is equal to the target specimen.…”
Section: Hotbox Test Window Test Piece and Comparison Hot Box Test Sy...mentioning
confidence: 99%
“…It was observed that the weight reduces while increasing the B 4 C particle content into the base metal. The distribution of hard particles in the matrix entails a higher resistance to abrasive wear that can be linked to reduced mating surface of the matrix and higher hardness of particles [25,29]. As such, the hard ceramic allows an improvement in the hardness of novel composite, which in turn prevents fast surface deterioration, finally driving better wear resistance of the composites [30].…”
Section: Wear Behaviourmentioning
confidence: 99%